A historical and etymological dictionary of American Sign Language : the origin and evolution of more than 500 signs - Shaw, Emily; Delaporte, Yves (Washington, DC : Gallaudet University Press, 2015)
"Utilizing 1,150 sign illustrations and historical texts, this reference presents the detailed account of the origins of more than 500 ASL signs, including regional variations"--
"Dictionary of all know texts featuring illustrations of early American Sign Language and historical images of French Sign language and linking them with contemporary signs"--
Includes bibliographical references (pages 325-330).
Keywords: American Sign Language -- Dictionaries; American Sign Language -- History; French Sign Language -- History